Measurement of deuteron spectra and elliptic flow in Pb–Pb collisions at √sNN=2.76 TeV at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2017)
The transverse momentum (pTpTp_T ) spectra and elliptic flow coefficient (v2v2v_{2}) of deuterons and anti-deuterons at mid-rapidity (|y|<0.5|y|<0.5|y|<0.5) are measured with the ALICE detector at the LHC in Pb-Pb collisions at sNN−−−√sNN\sqrt{s_{NN}} = 2.76 TeV. The measurement of the pTpTp_T spectra of (anti-)deuterons is done up to 8 GeV/c/c/c in 0-10% centrality class and up to 6 GeV/c/c/c in 10-20% and 20-40% centrality classes. The v2v2v_{2} is measured in the 0.8 < pTpTp_T < < <~5 GeV/c/c/c interval and in six different centrality intervals (0-5, 5-10, 10-20, 20-30, 30-40 and 40-50%) using the scalar product technique. Measured πππ ±±^{± }, K±±^{± } and p+p¯¯¯p¯\overline{p} transverse-momentum spectra and v2v2v_{2} are used to predict the deuteron pTpTp_T spectra and v2v2v_{2} within the Blast-Wave model. The predictions are able to reproduce the v2v2v_{2} coefficient in the measured pTpTp_T range and the transverse-momentum spectra for pTpTp_T > 1.8 GeV/c/c/c within the experimental uncertainties. The measurement of the coalescence parameter B2B2B_2 is performed, showing a pTpTp_T dependence in contrast with the simplest coalescence model, which fails to reproduce also the measured v2v2v_{2} coefficient. In addition, the coalescence parameter B2B2B_2 and the elliptic flow coefficient in the 20-40% centrality interval are compared with the AMPT model which is able, in its version without string melting, to reproduce the measured v2v2v_{2}(pTpTp_T ) and the B2B2B_2(pTpTp_T ) trend.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, S. Schuchmann, J. Stachel, D.F. Weiser, J. Wilkinson, B. Windelband, A. Zimmermann [und weitere]
Gesehen am 27.08.2018